The Effect of Drill Pass Training With The Inside of The Foot On The Accuracy of Futsal Passing SDN Bunter 1 - Permana, Muhammad Akkilasyah Subhan; Dinangsit, Dinar; Sudrazat, Adang (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the effect of drill pass training using the inside of the foot on the passing accuracy of SDN Bunter 1. The passing technique is one of the important techniques in futsal. The research method, One Group Pre-test and Post-test Design, is used to determine the difference before and after a certain treatment is given. The sample used in this study is the total sampling technique, which includes all students from grades IV, V, and VI at SDN Bunter 1. Using the ground passing test as an instrument in the research. The results of the normality test data processing yielded a pretest significance value of 0.143 and a posttest significance value of 0.291. From the data, it can be interpreted that the normality test is normally distributed, because the significance is > 0.05. Then the homogeneity test conducted resulted in a significance of 0.479. From the data, it can be interpreted that the homogeneity test is homogeneous. Then, a Paired Sample T-test was conducted to determine the effect, with a value of 0.000. So it can be said to have an effect because < 0.05. The research results show that passing accuracy skills (after using the drill pass training model) improved more compared to the initial test. This shows that the implementation of the drill pass training can improve the passing accuracy skills of SDN Bunter 1.